Perbedaan durasi perendaman ekstrak biji alpukat (persea americana) dan aquades pada resin akrilik heat cured - Nadya Annesa Yosefina; Nova Adrian (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Tooth loss has a negative impact on a person's quality of life such as pain, dissatisfaction with appearance and poor speech ability. Loss of teeth either partially or completely can be treated using dentures. One of the most commonly used dentures is polymethyl methacrylate. Acrylic resin has advantages such as good aesthetics and disadvantages can absorb liquids which can cause dimensional changes. Continuous use of acrylic resin can cause inflammation of the mucosal tissue such as denture stomatitis. Prevention of denture stomatitis by keeping dentures clean and cleaning dentures regularly. Denture cleaning can be done by using a toothbrush, soaking dentures in a disinfectant solution or both. The ideal denture cleaning agent has characteristics that do not damage the materials used in the manufacture of dentures including polymers. The use of safe cleaning agents derived from plants, one of which is avocado. Avocado seed extract (Persea americana) effectively inhibits microorganisms found in the oral cavity. Objective: To determine the effect of soaking in avocado seed extract (Persea americana) on dimension changes in heat cured acrylic resin. Methods: This type of research was a laboratory experiment with a group pretest-posttest design. The study was conducted on 32 rectangular specimens with a size of 20 x 10 x 3 mm. 32 specimens were divided into 2 groups, the first group with distilled water and the second group with avocado seed extract. Results: Data were collected using Friedman's test and Wilcoxon's follow-up test. It showed that there was a significant difference (p<0.05) in acrylic resin soaked in distilled water and avocado seed extract (Persea americana) after 1, 3, 5 and 7 days of immersion. Conclusion: There are differences in soaking in avocado seed extract (Persea americana) and distilled water against heat cured acrylic resin.